(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article synthesizes insights from language acquisition research and pedagogical theory to offer comprehensive guidance for educators working with young learners. It explores the developmental hurdles young learners encounter in speaking, such as limited vocabulary and pronunciation difficulties, and provides practical strategies for addressing these challenges. Additionally, it underscores the importance of motivation and engagement in language learning, offering evidence-based techniques to inspire young learners’ active participation. Moreover, the article advocates for ongoing professional development to equip teachers with the requisite skills and knowledge to effectively support young learners’ speaking skills development.